High N-glycan multiplicity is critical for neuronal adhesion and sensitizes the developing cerebellum to N-glycosylation defect - Medina-Cano, Daniel; Ucuncu, Ekin; Nguyen, Lam Son; Nicouleau, Michael; Lipecka, Joanna; Bizot, Jean-Charles; Thiel, Christian; Foulquier, François; Lefort, Nathalie; Faivre-Sarrailh, Catherine; Colleaux, Laurence; Guerrera, Ida Chiara; et al. (eLife, 2018)
Proper brain development relies highly on protein N-glycosylation to sustain neuronal migration, axon guidance and synaptic physiology. Impairing the N-glycosylation pathway at early steps produces broad neurological symptoms identified in congenital disorders of glycosylation. However, little is known about the molecular mechanisms underlying these defects. We generated a cerebellum specific knockout mouse for Srd5a3, a gene involved in the initiation of N-glycosylation. In addition to motor coordination defects and abnormal granule cell development, Srd5a3 deletion causes mild N-glycosylation impairment without significantly altering ER homeostasis. Using proteomic approaches, we identified that Srd5a3 loss affects a subset of glycoproteins with high N-glycans multiplicity per protein and decreased protein abundance or N-glycosylation level. As IgSF-CAM adhesion proteins are critical for neuron adhesion and highly N-glycosylated, we observed impaired IgSF-CAM-mediated neurite outgrowth and axon guidance in Srd5a3 mutant cerebellum. Our results link high N-glycan multiplicity to fine-tuned neural cell adhesion during mammalian brain development.
Gesehen am 25.03.2020